GLP-1 analogs: a comparison of new anti diabetic medications - presenting benefits and risks - Dębik, Marika; Szydłowski, Łukasz; Żurowska, Klaudia; Bednarski, Artur; Krużel, Aleksandra; Ziajor, Seweryn; Sajdak, Piotr; Tomasik, Justyna; Stodolak, Marcel; Kłos, Kamil (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Diabetes has emerged as a global lifestyle disease, with an alarming rise in cases, particularly of type 2 diabetes. In Poland, over 3 million people are diagnosed, and an estimated 4 million cases are expected by 2030. Effective treatment involves a multifaceted approach, including dietary intervention, physical activity, and pharmacological options. Incretins, such as glucagon-like peptide-1 (GLP-1), play a pivotal role in carbohydrate metabolism regulation, and GLP-1 analogs have become essential in managing type 2 diabetes. This paper explores the development and mechanisms of GLP-1 analogs, detailing their impact on insulin secretion, gastric emptying, and weight reduction. Description of the state knowledge: Various GLP-1 receptor agonists, including exenatide, liraglutide, dulaglutide, semaglutide, and the novel tirzepatide, are discussed. These drugs exhibit diverse pharmacokinetics, modes of administration, and effects on glucose metabolism and weight. Despite their efficacy, there is a concerning trend of off-label use, particularly for obesity treatment, leading to shortages for patients with valid prescriptions. This misuse is fueled by para-advertising on social media platforms, contributing to a surge in prescriptions and reimbursement costs. To address this, guidelines for GLP-1 analog use in obesity treatment are proposed, emphasizing the need for a stable drug supply and normalizing drug availability. Summary: In 2023, concerns intensified with reports of counterfeit GLP-1 analogs, prompting regulatory interventions. The paper concludes by underscoring the critical role GLP-1 analogs play in diabetes and obesity treatment, while emphasizing the importance of responsible prescription practices, guidelines adherence, and regulatory vigilance to ensure patient safety and mitigate the risks associated with misuse and counterfeit drugs.